Extraordinarily rapid proliferation of cultured muscle satellite cells from migratory birds - Young, Kevin; Regnault, Timothy; Guglielmo, Christopher (Zenodo, 2021)
Migratory birds experience bouts of muscle growth and depletion as they prepare for, and undertake prolonged flight. Our studies of migratory bird muscle physiology in vitro led to the discovery that sanderling ( Calidris alba ) muscle satellite cells proliferate more rapidly than other normal cell lines. Here we determined the proliferation rate of muscle satellite cells isolated from five migratory species (sanderling; ruff, Calidris pugnax western sandpiper, Calidris mauri yellow-rumped warbler, Setophaga coronata Swainson's thrush, Catharus ustulatus ) from two families (shorebirds and songbirds) and with different migratory strategies. Ruff and sanderling satellite cells exhibited rapid proliferation, with population doubling times of 9.3±1.3 and 11.4±2.0 hrs whereas the remaining species' cell doubling times were ≥24 hrs. The results indicate that the rapid proliferation of satellite cells is not associated with total migration distance but may be related to flight bout duration and interact with lifespan. The associated .Rmd and .html files are matched source and knitted output files describing the analysis and visualization process used to produce the results in this manuscript. The comments and explanations are self contained with the data description above.